Pupil-teacher gender interaction effects on scholastic outcomes in England and the USA - Andreas Ammermüller; Peter J. Dolton (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
The difference between girls and boys academic performance is a major issue on both sides of the Atlantic. Do boys and girls fair better with a teacher of their own gender? This paper investigates the presence of such ?pupil-teacher gender interactions? on scholastic performance. We use data from PIRLS and TIMSS on Reading, Science and Maths at grade 4 and grade 8 for England and the USA for data from 1995, 1999, 2001 and 2003. We find evidence of gender interaction effects in the form of both positive male interaction effects in Maths scores in the US and Science scores in England at grade 8. Further, using individual fixed effects, Gain score analysis of the difference between Maths and Science scores confirms the presence of Maths gender interaction effects in England (but not the USA) at grade 8 by 2003 when these effects were not present in 1995 or 1999.
Keywords: 330